Surface modification of Poly(p-phenylene terephthalamide) fibers by polydopamine-polyethyleneimine/graphene oxide multilayer films to enhance interfacial adhesion with rubber matrix. (September 2019) - Yang, Xuan; Tu, Qunzhang; Shen, Xinmin; Pan, Ming; Jiang, Chengming; Zhu, Pengxiao; Li, Yi; Li, Pei; Hu, Caibing
Abstract: In order to improve the interfacial adhesion between the poly(p-phenylene terephthalamide) fibers and rubber matrix while enhance the fiber strength simultaneously, a mild surface modification method was presented to graft polydopamine-polyethyleneimine/graphene oxide (PDA-PEI/GO) multilayer films onto the fiber surface. In this way, PDA could be first non-covalently deposited onto the fiber surface via dopamine biomimetic modification, and then the positively charged PEI was absorbed on the PDA through Michael addition reaction. After that, the negatively GO was grafted on the surface by the layer-by-layer (LbL) assembly to construct the PDA-PEI/GO multilayer films. The results of mechanical properties tests and pull-out force tests showed that the highest single-filament tensile strength and the highest pull-out force of the modified fibers increased by 15.1% and 78.1%, respectively. The optimal time of PEI/GO multilayer for the enhancement of adhesive properties was 7 and the excessive amount of PEI/GO would lead to high aggregation to decrease the adhesive strength. Graphical abstract: Image 1 Highlights: PPTA fibers are synergistically modified by dopamine, PEI and GO. Dopamine polymerization and LbL assembly are utilized together for the first time. The modification is so mild that it does not damage the fibers structure. The mechanical properties of fibers are improved obviously. The adhesive property of modified fibers with rubber increases by 78.1%.